IMPLIMENTASI MODEL PROLEM BASED LEARNING BERBASIS CULTURALLY RESPONSIVE TEACHING (PBL-CRT) UNTUK MENGEMBANGKAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA - Laily, Novia Islachul; Ismiati, Riza; Rosyidi, Abdul Haris; Mandala, Arif Sapta; Hanjarwati, Rante (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Research This study aims to develop students' mathematical creative thinking skills. junior high school students using problem-based learning model with Culturally Responsive Teaching (PBL-CRT) approach. The research This research is included in Classroom Action Research (PTK) which goes through 2 cycles. The research subject was the VII grade of SMPN 2 Candi Sidoarjo which amounted to 31 students. The research instruments used were tests and observations. Culture that shown with the Culturally Responsive Teaching approach are typical food in Sidoarjo and surrounding areas. The results showed that the PBL-CRT learning model can improve students' mathematical creative thinking skills. students' mathematical creative thinking skills, the N-Gain score obtained was 0.43 in cycle 1 and 0.60 in cycle 2 with a moderate category. in cycle 1 and 0.60 in cycle 2 with moderate category. Percentage of N-Gain score score percentage shows that the PBL-CRT learning model applied is quite effective in improving students' mathematical creative thinking skills.